CAUSAL AND CONCESSIVE ADJUNCTS IN PRESENT-DAY ROMANIAN: MODALITY AND EVIDENTIALITY - Bodoc, Alice Magdalena (PEOPLE: International Journal of Social Sciences, 2020)
The present study investigates the use of modality markers and subordinators in complex sentences with causal and concessive adjuncts from present-day Romanian. Cristofaro (2003), Longacre (2007), Nordström (2010), Kuroshima (2017), among others, bring evidence from different languages that modality and subordination have much in common, and, even more, that sometimes, certain subordinators can also function as modal markers (as they denote propositional modality – Nordström, 2010, p. 1). In this paper, I do not intend to defend nor to contradict Nordström’s hypothesis, but the purpose of my research is to explain how the modal markers and the subordinators influence each other, and, at the same time, how these elements influence the rest of the complex sentence. Furthermore, I intend to prove that the type of adjunct and/or the corresponding subordinating conjunction influence(s) the speaker’s selection of the adverbial modal marker, and also the selection of the verbal mood. To achieve this purpose, both a qualitative and quantitative analysis will be conducted on an electronic corpus